PENYULUHAN FISIOTERAPI TENTANG PENANGANAN MENURUNNYA KESEIMBANGAN AKIBAT DARI FLAT FOOT PADA ANAK-ANAK DI POSYANDU GPA KARANGPLOSO - Khaerunnisa, Fadhilah; Nanik Zainiyah,; Atika Yulianti, (JURNAL PENGABDIAN MANDIRI, 2025)
Flat foot is a flat foot shape caused by the loss of the medial longitudinal arch (inner sole of the foot). Flat feet can disrupt a person's balance because in this condition there is weakness in the internal muscles of the feet. Signs and symptoms that will arise due to flat feet are abnormal walking patterns that cause fatigue and problems with balance. Objectives: his counseling is carried out with the aim of providing education to children about flat feet, especially regarding the meaning, causes, as well as prevention strategies and physiotherapy exercises to reduce the number of flat foot disorders in children. Method: Posters are used as a tool to educate children about health problems related to flat feet. Consisting of 10 children, they were given a pretest and posttest before and after in the form of questions to measure children's understanding of the counseling material that had been delivered. Results: The counseling went well, and the children's understanding increased after attending physiotherapy education about flat feet. This outreach activity, carried out at Posyandu GPA Karangploso, Malang Regency, helps children understand more about flat feet and how to prevent and do physiotherapy exercises related to flat feet, such as heel raises exercise and towel curl exercise.. Conclusion:. To help children know and how to deal with flat feet, outreach activities have been carried out at Posyandu GPA Karangploso, Ngenep Village, Malang Regency. This counseling explains the heel raises exercise and towel curl exercise, which can be done at home to help with health problems related to flat feet. The majority of children who took part in this counseling said that they did not know what the effects of flat foot were or how to avoid it.